DEVELOPMENT OF MEDIA COMPETENCE IN PRESCHOOL STUDENTS: EUROPEAN EXPERIENCE (Comparative Professional Pedagogy, 2022)
The article defines the peculiarities of the development of media competence among students of preschool education in European countries, which is especially relevant under the conditions of implementing the Basic Standard of preschool education in Ukraine. The interpretation of the main definitions of «media education» and «media competence» by various scientists is given. It is justified that active dissemination of information and communication technologies, the decrease in the age of users of digital devices, and the sensitivity of the preschool period substantiate the relevance of our research. Media education is an integral part of the modern paradigm of European education. Learning with the help of digital media requires the adjustment of the content of media education. Modern educational institutions are faced with new tasks and new opportunities are emerging. Developing appropriate media competence is an important task. The peculiarities of the organization of media education in preschool educational institutions of such European countries as Germany, Austria, Finland, and Poland are considered. Documents on the education of European countries, which determine the relevance of the formation of media competence in students of preschool education, are analyzed. It is defined that in the system of preschool education, media education is not a separate discipline, despite the fact that among the competencies, the development of which is primary in the educational process, there are those that allow preschool children to actively use information technologies and interact in the digital environment. The reason for this is that the implementation of media education and the formation of media competence in children are not mandatory at most educational institutions although the use of information and communication technologies is provided during the educational process.Attention is focused on the need to develop media competence among students of preschool education, since from an early age children become active users of digital technologies and, as a result, they may have problems in the media space.
Keywords: media competence; media education; students of preschool education; system of preschool education; European countries